A Comparative Analysis of Structured Pedagogy Interventions in South Africa and Their Impact on Student Performance in Mathematics and Science Subjects - Malema, Julius (African Journal of Education and Practice, 2024)
Purpose: The aim of the study was to analyze the comparative analysis of structured pedagogy interventions in South Africa and their impact on student performance in mathematics and science subjects. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: A comparative analysis of structured pedagogy interventions in South Africa reveals that these targeted educational approaches have positively impacted student performance in mathematics and science subjects. Studies show that interventions such as curriculum-aligned teaching materials, teacher training, and standardized assessments significantly improved students' understanding and achievement in these areas. Unique Contribution to Theory, Practice and Policy: Constructivist learning theory, bloom’s taxonomy of educational objectives & sociocultural theory may be used to anchor future studies on the analyzing the comparative analysis of structured pedagogy interventions in South Africa and their impact on student performance in mathematics and science subjects. Schools should integrate structured lesson plans and data-driven instruction into everyday practice to enhance teacher efficacy and student performance. Policymakers should implement nationwide curriculum reforms that standardize content delivery across all schools, ensuring consistency in teaching quality, particularly in mathematics and science.